Screen Time, Anthropometric Parameter, Insulin and HOMA IR in Adolescents - Widjaja, Nur Aisiyah; Arifani, Rizka; Noviyanti, Tausiyah Rohmah; Alexander, Yoppi Yeremia; Hermanto, Edi; Iitdrie, Iitdrie; Ardianah, Eva; Keya, Rino Tryanto (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
The rapid integration of digital technology into daily life, particularly among adolescents, has generated increased screen time exposure. This study investigates the effect of screen time on anthropometric parameters, insulin levels, and HOMA IR in adolescents, regarding the increasing concerns about its potential health implications. Methods: A cross-sectional study involving 131 healthy adolescents (aged 12-18) was conducted to assess an anthropometric measurements, blood investigations (lipid profile, fasting blood glucose, fasting insulin), blood pressure, and screen time assessments. Screen time was categorized as recommended, moderate, and heavy. Results and Discussion: The moderate screen time was associated with a higher risk of overweight (OR=5.643), obesity (OR=3.737), insulin resistance (OR=4.116), and metabolic syndrome (OR=2.185). Heavy screen time showed higher risks for being overweight and metabolic syndrome (OR=32.421), but did not correlate significantly with overweight or obesity. The findings suggest a significant association between screen time and adverse health outcomes in adolescents, particularly for moderate and heavy screen time. Heavy screen time demonstrated substantial risks, emphasizing the need for interventions to mitigate potential health consequences. Conclusion: Screen time has noteworthy implications on the health of adolescents, with significant associations observed on anthropometric parameters, insulin resistance, and metabolic syndrome.